Effect of spirulina platensis algae purified bioactive peptides on wound healing after periodontal flap surgery: a randomized clinical trial - Parisa Jalali; Pouya Almasi; Masoumeh Faramarzi; Hamed Hamishehkar; Maryam Kouhsoltani (Scientific Reports)
Abstract Spirulina platensis, a blue-green alga rich in nutritional value and the beneficial pigment phycocyanin, is a source of bioactive peptides with antioxidant properties. This study aimed to evaluate the effects of bioactive peptides extracted from spirulina on wound healing and inflammation after periodontal surgery. In this double-blind, split-mouth randomized controlled trial study, twenty patients with periodontitis were assigned to either an experimental group (receiving spirulina peptide gel) or a control group (receiving placebo). Before surgery, all patients underwent scaling and root planning to eliminate pre-existing plaque. The surgical procedure involved a modified Widman flap technique. Wound healing was assessed at 1, 4, and 8 weeks post-surgery using parameters including soft tissue swelling, gingival color, probing depth, bleeding index, and plaque index. followed by a saline wash. Statistical analysis using SPSS 20 software employing non-parametric tests (Wilcoxon and Kruskal-Wallis) were carried out. The spirulina group showed a significant reduction in plaque and bleeding indices at weeks 4 and 8, as well as less gingival redness and lower pain scores at week 1, compared to controls. In addition, the need for pain medication was significantly lower in the spirulina group. These findings indicate that spirulina bioactive peptide gel can significantly improve wound healing, reduce inflammation, and alleviate post-surgical pain in periodontal procedures. These findings suggest its potential as a valuable adjunct therapy in periodontal surgery, enhancing patient recovery and improving overall periodontal health. However considering the limitation of the study, further studies are warranted to confirm and generalize the results.